Enhanced thermoelectric performance in polymorphic heavily Co-doped Cu2SnS3 through carrier compensation by Sb substitution. Issue 1 (31st December 2021) - Zhao, Yaqing; Gu, Yan; Zhang, Peng; Hu, Xiaohui; Wang, Yifeng; Zong, Peng'An; Pan, Lin; Lyu, Yinong; Koumoto, Kunihito
ABSTRACT: Heavily acceptor-doped Cu2 SnS3 (CTS) shows promisingly large power factor ( PF ) due to its rather high electrical conductivity ( σ ) which causes a modest ZT with a high electronic thermal conductivity ( κe ). In the present work, a strategy of carrier compensation through Sb-doping at the Sn site in Cu2 Sn0.8 Co0.2 S3 was investigated, aiming at tailoring electrical and phonon transport properties simultaneously. Rietveld analysis suggested a complex polymorphic microstructure in which the cation-(semi)ordered tetragonal phase becomes dominant over the coherently bonded cation-disordered cubic phase, as is preliminarily revealed using TEM observation, upon Sb-doping and Sb would substitute Sn preferentially in the tetragonal structure. With increasing content of Sb, the σ was lowered and the Seebeck coefficient ( S ) was enhanced effectively, which gave rise to high PF s maintained at ~10.4 μWcm −1 K −2 at 773 K together with an optimal reduction in κe by 60–70% in the whole temperature range. The lattice thermal conductivity was effectively suppressed from 1.75 Wm −1 K −1 to ~1.2 Wm −1 K −1 at 323 K while maintained very low at 0.3–0.4 Wm −1 K −1 at 773 K. As a result, a peak ZT of ~0.88 at 773 K has been achieved for Cu2 Sn0.74 Sb0.06 Co0.2 S3, which stands among the tops so far of the CTS-based diamond-like ternary sulfides. These findings demonstrate that polymorphic microstructures with cation-disordered interfaces as an approach to achieve effective phonon-blocking and low lattice thermal conductivity, of which further crystal chemistry, microstructural and electrical tailoring are possible by appropriate doping. Graphical Abstract: uf0001